EthoLeciplex: a new tool for effective cutaneous delivery of minoxidil. (2nd September 2022) - Elmowafy, Mohammed; Shalaby, Khaled; Alruwaili, Nabil K.; Elkomy, Mohammed H.; Zafar, Ameeduzzafar; Soliman, Ghareb M.; Salama, Ayman; Barakat, Elsaied H.
Abstract: This work designates EthoLeciplex, a vesicular system consisting of phospholipid, CTAB, ethanol and water, as an innovative vesicular system for cutaneous/transfollicular minoxidil (MX) delivery. MX-loaded EthoLeciplex was fabricated by one-step fabrication process. Formulations were designed to study the effects of drug/phospholipid ratio, CTAB/phospholipid ratio, and ethanol concentration on vesicular size, PDI, surface charge and EE%. The optimized formulation was characterized by in vitro release, drug/excipient compatibility, ex vivo skin permeability and safety. A size of 83.6 ± 7.3 to 530.3 ± 29.4 nm, PDI of 0.214 ± 0.01 to 0.542 ± 0.08 and zeta potential of +31.6 ± 4.8 to +57.4 ± 12.5 mV were observed. Encapsulation efficiency was obtained in its maximum value (91.9 ± 16.2%) at the lowest drug/phospholipid ratio, median CTAB/phospholipid and the highest ethanol concentration. The optimized formulation was consisted of 0.3 as drug/lipid ratio, 1.25 as CTAB/lipid ratio and 30% ethanol concentration and showed responses' values in agreement with the predicted results. Differential scanning calorimetry studies suggested that EthoLeciplex existed in flexible state with complete incorporation of MX into lipid bilayer. The cumulative amount of MX permeated from EthoLeciplex, conventional liposome and ethanolic solution after 12 h were 36.3 ± 1.5 µg/ml, 21 ± 2.0 µg/ml and 55 ± 4.0 µg/ml respectively. Based on the remaining amount, the amount of MX accumulated in different skin layers can be predicted in descending order as follows; EthoLeciplex > conventional liposome > MX solution. EthoLeciplex produced marked disorder in the stratum corneum integrity and swelling with no features of skin toxicity. This new cationic system is a promising carrier for cutaneous/transfollicular drug delivery.